Discrete Random Contention System with Variable Packet Length - Yingying Guo; Hongwei Ding; Jing Nan; Qianlin Liu (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
The paper researches the random contention system in-depth using the average cycle method, then gets the formulas of the systemic throughput, free rate and collision rate with variable packet length. The simulation results verify the correctness of the theory, meanwhile, gets some conclusions that the different arrival rate G is how to affect the main source of the throughput with variable packet length. It has some researching significance.  DOI: http://dx.doi.org/10.11591/telkomnika.v11i12.3697